African Immigrant Health: Prostate Cancer Attitudes, Perceptions, and Barriers. Issue 4 (August 2020) - Malika, Nipher; Ogundimu, Oyinkansola; Roberts, Lisa; Alemi, Qais; Casiano, Carlos; Montgomery, Susanne
Prostate cancer (PCa) is the second leading cause of cancer-related death among Black men who present with higher incidence, mortality, and survival compared to other racial groups. African immigrant men, however, are underrepresented in PCa research and thus this research sought to address that gap. This study applied a social determinants of health framework to understand the knowledge, perceptions, and behavioral tendencies regarding PCa in African immigrants. African immigrant men and women residing in different parts of the country (California, Texas, Colorado, Oklahoma, and Florida) from various faith-based organizations, African community groups, and social groups were recruited to participate in key informant interviews ( n = 10) and two focus groups ( n = 23). Four themes were identified in this study: (a) PCa knowledge and attitudes—while knowledge is very limited, perceptions about prostate health are very strong; (b) culture and gender identity strongly influence African health beliefs; (c) preservation of manhood; and (d) psychosocial stressors (e.g., financial, racial, immigration, lack of community, and negative perceptions of invasiveness of screening) are factors that play a major role in the overall health of African immigrant men. The results of this qualitative study unveiled perceptions, attitudes, beliefs, and knowledge of PCa among African immigrants that should inform the planning, development, and implementation of preventive programs to promote men's health and PCa awareness.